2021
DOI: 10.3389/fphys.2021.777259
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Metabolomic Profiling of Embryo Culture Medium Using Raman Spectroscopy With Deep Learning Model Predicts the Blastocyst Development Potential of Embryos

Abstract: Purpose: This study aimed to establish a non-invasive predicting model via Raman spectroscopy for evaluating the blastocyst development potential of day 3 high-quality cleavage stage embryos.Methods: Raman spectroscopy was used to detect the metabolic spectrum of spent day 3 (D3) embryo culture medium, and a classification model based on deep learning was established to differentiate between embryos that could develop into blastocysts (blastula) and that could not (non-blastula). The full-spectrum data for 80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…However, there are no studies exploring the combination of ML models and NMRderived metabolite data for predicting implantation potential. Recently, a deep learning model combined with Raman profiles generated from day-3 embryos was used to predict blastocyst development [23]. In line with the earlier results utilizing ML models for patient characteristics to predict embryo implantation potential [48][49][50], certain ML models (such as nearest neighbors, RBF SVM, decision tree, random forest, and neural net) provided accuracies of 50-67% (moderate accuracies) when metabolomic data alone was used.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, there are no studies exploring the combination of ML models and NMRderived metabolite data for predicting implantation potential. Recently, a deep learning model combined with Raman profiles generated from day-3 embryos was used to predict blastocyst development [23]. In line with the earlier results utilizing ML models for patient characteristics to predict embryo implantation potential [48][49][50], certain ML models (such as nearest neighbors, RBF SVM, decision tree, random forest, and neural net) provided accuracies of 50-67% (moderate accuracies) when metabolomic data alone was used.…”
Section: Discussionmentioning
confidence: 58%
“…The combination of "omics" technology and machine learning (ML) has been suggested to be able to improve ART outcome prediction [22]. A recent study demonstrated that combining a deep learning model with day-3 metabolite profiles predicted blastocyst development [23]. However, we believe that an accurate prediction of implantation potential has a higher clinical value than that of blastulation.…”
Section: Introductionmentioning
confidence: 97%
“…Again, the Raman peak at 512 cm −1 is attributed to the guanine molecule ring deformation [59]. Sharp peak at 1005 cm −1 is arising due to the stretching vibration of the aromatic ring present in the sample [61, 62]. The weak peaks at 1102 and 1692 cm −1 are attributed to PO2 symmetric stretching and CO stretching of uracil, respectively [63].…”
Section: Resultsmentioning
confidence: 99%
“…At present, the volume has been reduced to 20-25 μL. As a consequence, highly sensitive noninvasive techniques mainly from metabolomic method portfolio able to work with limited-volume samples (on the order of tenths or units of μL) such as near infrared and Raman spectroscopy-15 μL, NMR-18 μL, HPLC-MS-20 μL, and CE-LIF-10 μL [4][5][6][7] represent the best choice. Noninvasive techniques also include the study of the metabolic profile of blastocoele fluid [8] or the monitoring of fetal DNA released into the mother's blood [9].…”
Section: Introductionmentioning
confidence: 99%